Self-thinning dynamics in cork oak woodlands: providing a baseline for managing density - Fonseca, Teresa; Monteiro, Luísa; Enes, Teresa; Cerveira, Adelaide (Forest Systems, 2017)
Aim of study: The study aims to evaluate the maximum potential stocking level in cork oak (Quercus suber L.) woodlands, using the ecologically-based size-density relationship of the self-thinning law.Area of study: The study area refers to cork oak forests in mainland Portugal, distributed along its 18 districts from north to south.Material and Methods: A dataset with a total of 2181 observations regarding pure cork oak stands was collected from the Portuguese Forest Inventory (NFI) databases and from research plots. The dataset was subjected to two filtering procedures, one more restrictive than the other, to select the stands presenting the higher stocking values. The two resulting subsets, with 116 and 36 observations, from 16 and 10 districts of mainland Portugal, respectively, were then used to assess and describe the allometric relationship between tree number and their mean diameter.Main results: The allometric relationship was analysed and modelled using the log transformed variables. A slightly curvilinear trend was identified. Thus, a straight line and a curve were both fitted for comparison purposes. Goodness-of-fit statistics point out for a good performance when the data is set to the uppermost observed stocking values. A self-thinning line for cork oak was projected from the estimated relationship.Research highlights: The self-thinning model can be used as an ecological approach to develop density guidelines for oak woodlands in a scenario of increasing cork demands. The results indicate that the recommendations being applied in Portugal are far below the maximal potential stocking values for the species. It is therefore of the utmost importance to review the traditional silvicultural guidelines and endorse new ones.